The ties that bind: Bank relationships and small business lending - Santikian, Lori (Journal of Financial Intermediation, 2014)
The importance of bank relationships for small firms’ ability to raise external finance is well-documented, yet the mechanism through which relationships improve access to capital markets has received little empirical attention. This paper uses hand-collected, proprietary data from a mid-sized bank in the United States to identify the channels that strengthen the relationship between a small business and its bank. In contrast to earlier work that focuses on the role of relationships in alleviating information and incentive problems in lending, I find that the source of value in relationship banking is not limited to enhanced monitoring. Exploiting a unique feature of this dataset, I examine two channels of relationship strength that directly measure the stream of non-lending profits generated from (1) the non-credit services cross-sold to the borrower, and (2) the additional bank clients referred by the borrower. I document that non-lending profitability empirically determines the risk-adjusted terms of lending. In models of loan price that already include both the bank’s proprietary risk rating and traditional risk proxies, non-lending profits significantly improve explanatory power and account for up to half of the total explained variation. Conditional on risk profile, a one-standard deviation increase in aggregate non-lending profits lowers the loan interest rate by 32 basis points and increases access to credit by 26%.